Bimbingan Belajar melalui Bermain Peran Berbasis Islam untuk Meningkatkan Kecerdasan Emosional AUD - Nuraini, Paramita; Tawil, Tawil (Universitas Muhammadiyah Magelang, 2017)
This study aims to determine the influence of learning guidance services through role-based play Islam on improving emotional intelligence. The study was conducted on the students of PAUD Amanah Magelang city. This study uses an experimental design that is a pretest-posttest design of one group. Samples to be taken as many as 7 students who have tendency of low emotional intelligence. Using purposive sampling sampling technique. Methods of data collection in self directed learning survey. Data analysis using non parametric statistic with wilcoxon test with SPSS version 17.0 for windows. The results showed that the differences in self-learning before and after students using guidance services through role-based learning is proven with a pretest average score of 164.60 and a post test of 177.00 has differences in average pretest score and posttest score of 12.4 With an average increase of 20%. Based on it can be concluded that training using Islamic role-based play can improve students' emotional intelligence.